Neurovascular Adverse Effects of Sars-Cov-2 Vaccination - Panos LD; Bargiotas P; Hadjigeorgiou G; Panos GD (Dove Medical Press, 2024)
Leonidas D Panos,1,2 Panagiotis Bargiotas,2 Georgios Hadjigeorgiou,2 Georgios D Panos3,4 1Department of Neurology, Bern University Hospital « Inselspital », Bern, Switzerland; 2Department of Neurology, School of Medicine, University of Cyprus, Nicosia, Cyprus; 3Department of Ophthalmology, Queen's Medical Centre, Nottingham University Hospitals (NUH), Nottingham, U.K; 4Division of Ophthalmology and Visual Sciences, School of Medicine, University of Nottingham, Nottingham, U.KCorrespondence: Leonidas D Panos, Department of Neurology, Bern University Hospital "Inselspital", Freiburgstrasse 16, 3010, Bern, Switzerland, Tel +41 31 632 70 00, Email ldpanos@yahoo.gr Georgios D Panos, Department of Ophthalmology, Queen's Medical Centre, NUH, Derby Road, Lenton, Nottingham, NG7, 2UH, UK, Tel +44 115 924 9924, Email gdpanos@gmail.comAbstract: The global deployment of SARS-CoV-2 vaccines has been pivotal in curbing the COVID-19 pandemic, reducing morbidity and mortality associated with the virus. While most of these vaccines have demonstrated high efficacy and overall safety, emerging reports have highlighted potential neurovascular adverse effects, albeit uncommon, associated with these vaccinations. This review aims to assess and summarize the current knowledge on the neurovascular complications arising post-SARS-CoV-2 vaccination. We conducted an extensive literature review, focusing on clinical studies and case reports to identify reported neurovascular events, such as ischemic stroke, cerebral sinus venous thrombosis, intracerebral hemorrhage, pituitary apoplexy and primary CNS angiitis Despite the relative rarity of these events, their impact on affected individuals underscores the importance of ongoing surveillance, early detection, and management strategies. We aim to provide healthcare professionals with the latest evidence on neurovascular adverse effects, facilitating informed decision-making in the context of SARS-CoV-2 vaccination programs. Furthermore, we highlight areas requiring further research to understand the pathophysiology of these adverse events better and to develop targeted prevention and treatment strategies.Keywords: neurovascular adverse effects, COVID-19, vaccines, SARS-CoV-2, coronavirus, pandemic, BNT162b2, mRNA-1273, ChAdOx1, NVX-CoV2373